EEG Based Epilepsy Seizure Analysis and Classification Methods: An Overview - Kukker, Amit; Sharma, Rajneesh (International Journal of Computer Sciences and Engineering, 2019)
Epilepsy has always baffled humans, in particular, the approach one needs to take for curing or at least subside its severity. Epilepsy is a continual lingering neurological ataxia generated by intermittent, transient, superfluous, wanton and unfounded seizures. Epilepsy never indicates cause of a person`s seizures or their severity. Electroencephalogram (EEG) is the tool of choice for analysis and diagnosis of epilepsy along with different automatic and visual inspection techniques. Several researchers have proposed diverse techniques for classification and analysis of epilepsy. Different pre-processing, feature extraction and classification approaches are presented. This paper attempts to catalogue various techniques and algorithms proposed so far for epileptic seizure analysis along with shortcomings thereof to facilitate further research in this complex area. This will help in online seizure detection and timely diagnosis.